Identification of 3D printer firmware applying brushless direct current motor servo with step G-code reading and executing method - Setiawan, Budhy; Siradjuddin, Indrazno; Palupi, Resti Dyah Ayu Retno (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is a large-scale Cartesian 3D printer with a build volume of 2 × 2 × 2 meters, equipped with BLDC servo motors on the X and Y axes, a NEMA 34 stepper motor on the Z axis, and a NEMA 17 stepper motor for filament extrusion. The main problem addressed is the limitation of existing firmware, which only supports bipolar stepper motors (NEMA standard), making it unsuitable for achieving the higher extruder speeds required in large-format printing. To overcome this issue, a new firmware was designed to support brushless direct current (BLDC) servo motors, enabling faster, more stable, and more precise motion control. The developed firmware, based on the ESP32 microcontroller, processes G-code instructions step by step, calculates motor commands, and communicates them to BLDC motor drivers (FSESC 4.12 on the VESC platform) with encoder feedback for accurate positioning. Experimental results demonstrated reliable synchronization of the X and Y axes across different speeds and distances, with average positioning errors of 0.9% on the X-axis and 1.03% on the Y-axis. The system operated stably within a rotational speed range of F8000–F54000 (1000–7000 RPM) and a printing speed range of 92–800 mm/s, confirming the firmware’s capability to handle both low- and high-speed operations. The interpretation of the results provides superior acceleration, precision, and stability compared to stepper-motor-based systems. A distinctive feature of this work lies in adapting G-Code step execution for BLDC motors, which has not been widely implemented in existing 3D printing firmware. The practical significance of the results is the potential application of this firmware in large-scale and high-speed 3D printers. This makes the approach highly relevant for advanced manufacturing industries where precision, scalability, and efficiency are critical